Saudi Arabia guarding the desert kingdom - Cordesman, Anthony H. 1939-2024 (CSIS Middle East dynamic net assessment, 1997)
Since the Gulf War, Saudi Arabia's tenuous security situation has been altered by an ongoing U.S. presence. This volume provides detailed analysis of the state of the Saudi economy and military forces, its growing internal security problems and the stability of its regime, and its reliability as an energy exporter.